A historical review of the classification of Erebinae (Lepidoptera: Erebidae) - Homziak, Nicholas T.; Breinholt, Jesse W.; Kawahara, Akito Y. (Zootaxa, 2016)
Erebidae is one of the most diverse families within the order Lepidoptera (butterflies and moths), with nearly 25,000 described species. The nominal subfamily Erebinae is among the most species rich and taxonomically complex. It reaches its highest diversity in the tropics, where much of the fauna remains undescribed. Species in this subfamily feed on a broad range of host plants, with associated radiations on grasses and legumes, and some species are pests of agriculture and forestry. The Erebinae, as defined today, comprises a large portion of the former noctuid subfamily Catocalinae. However, many lineages have tenuous or uncertain systematic placement. Here, we review the complex historical classification of Erebinae, and discuss the possible placement of some of these lineages in light of traditional morphological groupings and recent molecular phylogenetic analyses. We present an updated list of named erebine tribes and their relationships, and identify morphological traits from literature used to group genera within these tribes.